Verzameling Tony Herbert - Collection Tony Herbert - Sammlung Tony Herbert, Blankenberge. (Kortrijk : Drukkerij Jos. Vermaut)
Anthoons, Willy ; van den Berghe, Frits ; Bertrand, Gaston ; Bonnet, Anne ; Brusselmans, Jean ; Burssens, Gaston ; Cantré, Jozef ; Daeye, Hippolyte ; Delvaux, André ; Grard, Georges ; Herbert, Tony ; Jespers, Oscar ; Leplae, Charles ; Van Lint, Louis ; Mendelson, Marc ; Permeke, Constant ; Puvrez, Henri ; De Smet, Gust ; Tytgat, Edgard ; de Woestyne, Gustave Van ; Wouters, Rik
boek
Keywords: Herbert, Tony